Out‐of‐hospital versus in‐hospital status epilepticus: The role of etiology and comorbidities. (8th July 2022) - Brigo, Francesco; Turcato, Gianni; Lattanzi, Simona; Orlandi, Niccolò; Turchi, Giulia; Zaboli, Arian; Giovannini, Giada; Meletti, Stefano
Abstract: Background and purpose: Our objectives were to identify differences in clinical characteristics between patients with out‐of‐hospital and in‐hospital status epilepticus (SE) onset, and to evaluate the influence of SE onset setting on 30‐day mortality and SE cessation. Methods: We included consecutive patients with SE admitted from 2013–2021 at Modena Academic Hospital. A propensity score was obtained with clinical variables unevenly distributed between the two groups. Results: Seven hundred eleven patients were included; 55.8% (397/711) with out‐of‐hospital and 44.2% (314/711) with in‐hospital onset. Patients with in‐hospital SE onset were older and had a higher frequency of comorbidities, acute and/or potentially fatal etiologies, impaired consciousness before treatment, and nonconvulsive or myoclonic SE. No difference was found in SE cessation between the groups. Patients with in‐hospital SE had higher 30‐day mortality (127/314, 62.9% vs. 75/397, 37.1%; p < 0.001). In‐hospital onset was an independent risk factor for 30‐day mortality (adjusted odds ratio = 1.720; 95% confidence interval = 1.107–2.674; p = 0.016). In the propensity group ( n = 244), no difference was found in 30‐day mortality and SE cessation between out‐of‐hospital and in‐hospital SE onset groups (36/122, 29.5% vs. 34/122, 27.9%; p = 0.888; and 47/122, 38.5% vs. 39/122; 32%; p = 0.347, respectively). Conclusions: In‐hospital SE is associated with higher 30‐day mortality without difference in SE cessation. The two groups differ considerably for age, acute and possibly fatal etiologies, comorbidities, and SE semiology. The patient location at SE onset is an important prognostic predictor. However, the increased mortality is probably unrelated to the setting of SE onset and reflects intrinsic prognostic predictors. Abstract : The patient location at status epilepticus (SE) onset is an important prognostic predictor of 30‐day mortality. However, the increased mortality is probably unrelated to the setting of SE onset and reflects intrinsic prognostic predictors.